2010
DOI: 10.1186/1471-2407-10-301
|View full text |Cite
|
Sign up to set email alerts
|

SNAI2/Slug promotes growth and invasion in human gliomas

Abstract: BackgroundNumerous factors that contribute to malignant glioma invasion have been identified, but the upstream genes coordinating this process are poorly known.MethodsTo identify genes controlling glioma invasion, we used genome-wide mRNA expression profiles of primary human glioblastomas to develop an expression-based rank ordering of 30 transcription factors that have previously been implicated in the regulation of invasion and metastasis in cancer.ResultsUsing this approach, we identified the oncogenic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 27 publications
(34 reference statements)
8
106
1
Order By: Relevance
“…A recent report has shown that miR-124a and miR-203 play critical roles in cancers (43)(44)(45)(46)(47). Furthermore, SLUG acts as a predictive marker for the clinical outcome of patients with lung adenocarcinoma, breast, ovarian, colon, and gastric cancers (43,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that miR-124a and miR-203 play critical roles in cancers (43)(44)(45)(46)(47). Furthermore, SLUG acts as a predictive marker for the clinical outcome of patients with lung adenocarcinoma, breast, ovarian, colon, and gastric cancers (43,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…40,56 Snail/Slug proteins have already been involved in GBM invasion. 57,58 We demonstrate the regulation of Snail/Slug, in parallel to increased PY142 b-catenin, upon stimulation of GBM cells with HGF. Statistical studies indicate that both nuclear Snail/ Slug and nuclear PY142 b-catenin peak in astrocytomas of grade III.…”
Section: Resultsmentioning
confidence: 99%
“…In GBM, the Rho family GTPase (RND)-3 has been shown to promote the degradation of SNAIL in vitro and in vivo, while downregulation of RND3 strongly induces SNAIL expression and migration (166). SLUG expression was found to correlate with histologic grade and invasive phenotype in glioma, whereas knockdown of SLUG attenuated invasion and prolonged survival in an intracranial mouse model (167).…”
Section: Twist Snail Slug and Zebmentioning
confidence: 99%